Livro do negro (2020-2021): relatos e reflexões acerca da apropriação do romance “Bom Crioulo”, de Adolfo Caminha em um processo de criação pessoal - Souza, José Henrique Rodrigues de (2022)
The present research features the Creation Process of an artist book entitled "Livro do Negro", carried out between 2020 and 2022. The analysis of the process is based on the presentation of ideas and procedures, connections of the work in process with works by other artists, as well as studies the initial support of the object, the book Bom Crioulo, by Adolfo Caminha, read in different contexts. From the discussion of the Creation Process and its technical operations, it was possible to determine some of the representation patterns, technical choices and subversions and other singularities of the process. The theoretical research is based on two readings: one carried out during high school and another during the new coronavirus (COVID-19) pandemic. The artistic making allowed theoretical research to appropriate studies from other fields of knowledge as a possibility to understand the stages of this process. A contextualization of the period in which Caminha's novel was published allowed for an understanding of the contemporary reception of publications whose themes escape hegemonic heterosexuality. The study of the history of reading allowed the understanding of the personal reasons involved in the operation of reading, the personal relationships with this act, while the approximation of the artistic object presented with other works of art allowed the discussion with other relationships between the book of artist and books by other artists.